2020
DOI: 10.3390/biomedicines8030065
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Aberrantly-Expressed Long Non-Coding RNAs in Osteoblastic Cells from Osteoporotic Patients

Abstract: Osteoporosis (OP) is a multifactorial disease influenced by genetic, epigenetic, and environmental factors. One of the main causes of the bone homeostasis alteration is inflammation resulting in excessive bone resorption. Long non-coding RNAs (lncRNAs), have a crucial role in regulating many important biological processes in bone, including inflammation. We designed our study to identify lncRNAs misregulated in osteoblast primary cultures derived from OP patients (n = 4), and controls (CTRs, n = 4) with the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Our study further confirms and extends this hypothesis demonstrating that the circulating GAS5 level is significantly increased in OP patients, specifically in subjects presenting fragility fractures. GAS5 expression level was found downregulated in hMSCs [ 24 ] and primary osteoblasts [ 9 ] from OP patients and its overexpression significantly induced ALP activity and promoted osteogenic differentiation of hMSCs through RUNX2 induction [ 24 ]. Moreover, Wang et al, by using an osteoporotic-induced mouse model, observed that GAS5 expression was increased during the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) via negatively modulating miR-135a-5p to induce FOX1 expression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study further confirms and extends this hypothesis demonstrating that the circulating GAS5 level is significantly increased in OP patients, specifically in subjects presenting fragility fractures. GAS5 expression level was found downregulated in hMSCs [ 24 ] and primary osteoblasts [ 9 ] from OP patients and its overexpression significantly induced ALP activity and promoted osteogenic differentiation of hMSCs through RUNX2 induction [ 24 ]. Moreover, Wang et al, by using an osteoporotic-induced mouse model, observed that GAS5 expression was increased during the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) via negatively modulating miR-135a-5p to induce FOX1 expression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are important regulators of bone metabolism and changes in their expression pattern are linked to OP pathogenesis [ 7 , 8 ]. Recently, we demonstrated that lncRNAs involved in inflammatory responses are deregulated in cells from OP patients compared to controls [ 9 ]. Among them, the lncRNA growth arrest-specific transcript 5 (GAS5, MIM: #608280), encoded by the GAS5 gene at 1q25, has shown a five-fold downregulation of OP primary osteoblasts, thus indicating a possible role in OP [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective estrogen receptor modulators (SERMs) act on estrogen receptors with agonist or antagonist activity, depending on the tissue type. Raloxifene (RLX) is an SERM used for the treatment of postmenopausal osteoporosis (OP) because of its activity as an estrogen receptor agonist in bone [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The effect of RLX can be tissue- or species-specific [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of lncRNAs have been shown to interact with miRNAs during osteoblast differentiation [97]. H19/miR-675 was reported to suppress mRNA and protein expression of transforming growth factor-β1 (TGF-β1) and histone deacetylase (HDAC) 4/5.…”
Section: Interactions Between Lncrnas and Mirnasmentioning
confidence: 99%